A modified bipolar translinear cell with improved linear range and its applications - Merz, Naruemo; Kiranon, Wiwat; Wongtachathum, Chariya; Pawarangkoon, Prajuab; Narksarp, Wipavan (My University, 2012)
This paper presents a technique to extend the linear input voltage range of a sinh mixed translinear cell proposed by Fabre [1]. This technique extends the linear operation range of the circuit by inserting common-anodeconnected pairs into the mixed translinear cell. Then the relationship between the output current and the input voltage is developed to be linear. The transconductance gain can be adjusted electronically while keeping its linearity. The performance of the proposed circuit is verified by mathematical analysis and by SPICE simulations. Finally, applications of the proposed cell in a floating resistor and a CCCII for designing an instrumentation amplifier are presented.
Keywords: Analog integrated circuit; Linearization; Transconductance; Translinear circuit